Changing tides twilight and dawn in the Spanish Sea, 1763 - 1803 - Weddle, Robert S. (Association of Former Students, Texas A and M University: The centennial series of the Association of Former Students, Texas A and M University, 1995)
"Well-organized and clearly written, this volume, the third part of a history of the Gulf of Mexico in the Spanish colonial era, rests on a thorough integration of secondary publications with the author's archival research. The first part of series is Spanish Sea: Gulf of Mexico in North American discovery (1985); second part is The French thorn: rival explorers in the Spanish Sea, 1682-1762 (1991)"--Handbook of Latin American Studies, v. 58.. - http://www.loc.gov/hlas/